The Most Effective Leadership Styles in Arab Universities, as Perceived by Academics, with Application to Universities In Saudi Arabia, Sudan, Egypt, Iraq, And Morocco - Ahmed, Abdelnassir Talab Hassan (Journal of Ecohumanism, 2025)
This study examined the prevalence of effective leadership styles in Arab universities from the perspective of academic staff. Using a descriptive-analytical approach, it employed a 45-item questionnaire covering transformational, spiritual, servant, transactional, and passive leadership. Findings showed that leadership styles were generally present at a high level, with an overall mean of 3.46 (69%). Transformational leadership ranked highest (4.10, 82%), followed by spiritual (4.06, 81%), servant (3.98, 80%), and transactional (3.66, 74%). Passive leadership ranked lowest (1.51, 30%). Among the studied countries, Saudi Arabia exhibited the highest leadership effectiveness, followed by Morocco, Iraq, Egypt, and Sudan. No statistically significant differences were found between male and female faculty members regarding leadership style rankings.